Genetic markers associated with host status and clonal expansion of Group B Streptococcus in the Netherlands - Khan, Uzma Basit; Dyster, Victoria; Chaguza, Chrispin; van Sorge, Nina M.; van de Beek, Diederik; Man, Wing Kit; Bentley, Stephen D.; Bijlsma, Merijn W.; Jamrozy, Dorota (Frontiers in Microbiology, 2024)
Certain Group B Streptococcus (GBS) genotypes are associated with invasive disease in neonates. We conducted a comparative genomic analysis of GBS isolates from neonatal disease and maternal carriage in the Netherlands to determine distribution of genetic markers between the two host groups.Whole genome sequencing was used to characterise 685 neonatal invasive isolates (2006 -2021) and 733 maternal carriage isolates (2017 -2021) collected in the Netherlands.Clonal complex (CC) 17 and serotype III were significantly more common in disease while carriage isolates were associated with serotypes II, IV, V as well as CC1. Previously reported CC17-A1 sub-lineage was dominant among disease isolates and significantly less common in carriage. The phiStag1 phage, previously associated with expansion of invasive CC17 isolates in the Netherlands, was more common among disease isolates compared to carriage isolates overall, however it was equally distributed between CC17 isolates from carriage and disease.Prevalence of antimicrobial resistance genes was overall lower in disease compared to carriage isolates, but increased significantly over time, mediated by rise in prevalence of a multidrug resistance element ICESag37 among disease isolates.There is a stable association between certain GBS genotypes and invasive disease, which suggests opportunities for developing more precise disease prevention strategies based on GBS targeted screening. In contrast, GBS mobile genetic elements appear less likely to be correlated with carriage or disease, and instead are associated with clonal expansion events across the GBS population.